Direct synthesis of N, S co-doped porous carbons using novel organic potassium salts as activators for efficient CO2 adsorption. (15th June 2023) - Cui, Hongmin; Shi, Jinsong; Xu, Jianguo; Yan, Nanfu; Liu, Yuewei
Graphical abstract: Highlights: NSCDCs are prepared with novel organic potassium salts as tri-functional activators. The organic potassium salts act as activator, N source, and S source simultaneously. The NSCDCs exhibit high surface area and tunable N/S content. At 25 °C and 20 bar, CO2 uptake of the NSCDCs reaches 17.29 mmol/g. Abstract: In the current work, we proposed the use of two organic potassium salts, 4-morpholineethanesulfonic acid (MES) potassium salt and 1, 4-piperazinediethanesulfonic acid (PIPES) dipotassium salt, as novel and tri-functional activators for the synthesis of N, S co-doped carbons (NSCDCs). The organic potassium salts served as activator and N/S source at the same time, allowing direct synthesis of NSCDCs with N/S free precursor. In order to verify this hypothesis, N, S free hydrochar derived from glucose was selected as the carbon source. NSCDCs with high and tunable surface area (1673–2235 m 2 /g), N content (3.44–5.80 wt%), and S content (5.26–8.72 wt%) were obtained. Physicochemical properties of the carbons were mainly decided by potassium salt and activation temperature. The NSCDCs were also investigated for their CO2 adsorption properties. At 25 °C and 1 bar, high CO2 uptake of 3.04–3.99 mmol/g was achieved by the carbons. Qst of the NSCDCs was 22.6–28.7 kJ/mol, and CO2 adsorption selectivity over N2 was 10.5–17.3 at 25 °C and 1 bar. At 25 °C and 20 bar, CO2 uptake increased to 11.26–17.29 mmol/g, and exhibited linear dependence on specific surface area. The current work indicated that MES potassium salt/PIPES dipotassium salt could be used as activator for convenient synthesis of NSCDCs as efficient CO2 adsorbents.